2022
DOI: 10.3389/fenrg.2021.806926
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Green Innovation on Firm Value: Evidence From Listed Companies in China’s Heavy Pollution Industries

Abstract: The unspecified impact of green innovation on corporate financial performance has made some enterprises delay green innovation investment plans, and even abandon green innovation. Mitigating the economic concerns faced in the process of green innovation decision-making is of great significance to accelerate the process of enterprises’ green transformation. Using an unbalanced panel data of Chinese heavy pollution listed companies from 2008-2017, this paper investigates the impact of green innovation on firm va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 101 publications
(135 reference statements)
1
21
0
5
Order By: Relevance
“…Based on the previous studies ( Chen and Wan, 2020 ; Chen and Ji, 2022 ; Liao et al, 2022 ; Xie et al, 2022 ), this study establishes Equation 1 and use the OLS regression method to investigate the impact of CSR on the sustainable innovation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous studies ( Chen and Wan, 2020 ; Chen and Ji, 2022 ; Liao et al, 2022 ; Xie et al, 2022 ), this study establishes Equation 1 and use the OLS regression method to investigate the impact of CSR on the sustainable innovation.…”
Section: Methodsmentioning
confidence: 99%
“…It is common knowledge that significantly polluting companies have a far greater detrimental influence on the ecological environment than others do ( Xie et al, 2022 ). Because of China’s large consumption of traditional fossil fuels, the country’s environmental quality has worsened significantly, attracting the international community’s utmost concern ( Dong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the influence of possible confounding factors, this paper refers to the existing literature and controls for a series of control variables: (1) the level of corporate governance (Bsize), which is determined by the number of boards of directors, because it is generally accepted that businesses with higher levels of corporate governance are more effective in technological innovation ( Sapra et al, 2014 ; Liu et al, 2020 ); (2) Independence of the board of directors (Bratio), which is measured by the number of independent directors as a percentage of the total number of directors, can increase the market dynamics of the company and thus encourage the company to engage in more R&D and innovation activities ( Balsmeier et al, 2017 ; Nguyen et al, 2020 ); (3) The maximum shareholder ownership ratio (Sratio), which is considered that a moderate shareholding ratio will stimulate a convergence of interests and thus promote R&D innovation, while too high a shareholding ratio will have a management defense effect and inhibit technological innovation ( Mengli and Yongming, 2020 ); (4) Enterprise development prospects (Future), it is generally believed that more promising companies are more willing to conduct innovative R&D. The growth rate of revenue is used to measure the development capability and prospect of the company ( Aguilera-Caracuel and Ortiz-de-Mandojana, 2013 ; Xie et al, 2022 ); (5) Firm size (lnAsset), the study concluded that the larger the firm is, the higher its innovation success rate will be, using the logarithm of total assets at year-end to measure firm size ( Daksa et al, 2018 ; Liu et al, 2021 ); (6) Corporate debt (Lev), which makes it more difficult to carry out corporate innovation activities when a company is in a poor financial position, using the ratio of total debt to total assets to measure a company’s indebtedness ( Iqbal et al, 2020 ); (7) The maturity of the company (Age), research shows that longer established companies have a stronger sense of innovation, and the age of the company is chosen to measure the maturity of the company ( Bianchini et al, 2018 ; Nguyen et al, 2020 ); (8) Corporate profitability (Share), research shows that the more profitable companies have a competitive advantage in innovation, using earnings per share to measure corporate profitability ( Nguyen et al, 2020 ). Descriptive statistics for each variable are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…According to some academics, increasing the degree of green innovation can successfully improve the energy consumption structure of businesses ( Jiang et al, 2020 ; Yang et al, 2021a ), raise energy utilization efficiency ( Sun et al, 2019 ; Yang et al, 2022 ), and decrease the intensity of pollutant emissions ( Dong et al, 2022 ; Yi et al, 2022 ; Ren et al, 2022b ), and the intensity of pollutant emissions, all of which will raise people’s quality of life ( Aguilera-Caracuel and Ortiz-de-Mandojana, 2013 ; Amore et al, 2015 ; Burlea-Schiopoiu et al, 2022 ). Additionally, businesses that invest in green innovation can boost their financial performance ( Rezende et al, 2019 ; Xie et al, 2022 ), environmental performance ( Singh et al, 2020 ), and competitive advantages ( Barforoush et al, 2021 ). Second, internal corporate drives and external environmental forces have been examined when examining the drivers of green innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Patent application data perform better than granted patent data in reflecting a firm's innovation output level (Ernst, 2001). By using Xie's research method (Xie et al, 2022), the total number of green patent applications and green invention patent applications are proxy variables for the number of green technology innovations (INNO 1 ) and the quality of green technology innovation (INNO 2 ), respectively.…”
Section: Green Technology Innovationmentioning
confidence: 99%